Implementasi Search Engine Optimization Pada Website Wisata Edukasi Gunung Laos Untuk Meningkatkan Hasil Search Engine Result Page - Hanif Satria (Infoman's : Jurnal Ilmu-ilmu Manajemen dan Informatika, 2021)
Mount Laos Tourism is a new tourist site, as a tourist attraction that has not been visited for along time is certainly needed for visitors both from visitors who are close to the location and farfrom the location. According to Mr. Imam as the manager or tourism pioneer when conductingan interview on Mount Laos Education Tourism in terms of promotion, it has used social mediasuch as Facebook, Instagram and Google Business, but as a new tour in terms of promotion ofthe latest news that is fast and detailed. Seeing this potential, researchers conducted research tocreate a web site as a promotional medium that was optimized with Search Engine Optimization(SEO) with On Page and Off Page techniques. The focus in this research is a website that isoptimized by Search Engine Optimization (SEO) techniques, web site design using WordPressCMS. In implementing SEO On Page researchers use Ubersuggest tools, Google Analytics andWhatsmyserp. While in the implementation of Off Page SEO researchers create links (backlinks)to several websites that have high trust, one of them like .go.id. The results of this research arethe https://wisatagununglaos.com/ website which has been optimized by Search EngineOptimization (SEO) and Google search page one.